Ellipsis and Substitution in Spontaneous Spoken Language: A Case Study of Jubilee YouTube Channel Videos - Vestalira Maharani, Zielda; Zewitra (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2024)
This study investigates the occurrence of ellipsis and substitution in spontaneous spoken language. By employing the textual qualitative method, the study analyzed 106 conversational texts obtained from videos on the Jubilee YouTube channel. The research reveals that speakers frequently use ellipses and substitutions in their spontaneous spoken language to establish cohesion in their utterances. Nominal ellipsis has the highest occurrence with 50 data across all forms (nominal, verbal, and clausal ellipsis as well as nominal, verbal, and clausal substitution), indicating speakers’ propensity to avoid repetition, especially in nominal elements. Meanwhile, in terms of substitution, speakers are more likely to substitute their verbal elements, forming verbal substitution (occurred in 17 cases), in order to form variance in their utterances. This study provides fruitful significance, both theoretical and practical, and they will be further explained in this article.